Experimental study rheological behavior of MWCNT (10%)-TiO2 (90%)/SAE40 hybrid nano-lubricants (HNLs) post-processing of the results with response surface methodology (RSM) - Esfe, Mohammad Hemmat; Alidoust, Soheyl; Esfandeh, Saeed; Toghraie, Davood; Ardeshiri, Erfan Mohammadnejad (The Korean journal of chemical engineering, 2023)
In this study, which was approached with an industrial approach, for the first time, the rheological behavior of hybrid nano-lubricants (HNLs) with the formulation MWCNT (10%)-TiO 2 (90%)/SAE40 was investigated experimentally, statistically and numerically. Nano-solution study conditions were performed in six solid volume fractions (=0.0625% to 1%) and a temperature range of T=25 to 50 °C. Quantitative statistics of laboratory studies show that the maximum and minimum viscosity of HNLs relative to the base oil increase and decrease by 29.6%, −13.40%, respectively. To predict the experimental data, to provide a correlation relationship and to establish a relationship between the target response and the effective variables, response surface methodology (RSM) with a three-point model and coefficient of determination 0.9986 was used.